2014
DOI: 10.1093/abbs/gmu044
|View full text |Cite
|
Sign up to set email alerts
|

The anorexic effect of Ex4/Fc through GLP-1 receptor activation in high-fat diet fed mice

Abstract: Exendin-4 (Ex4), a peptide initially found in the saliva of the Gila monster, can activate the signaling pathway of the incretin hormone glucagon-like peptide-1 (GLP-1) through the GLP-1 receptor (GLP-1R). We previously reported that a chimera protein consisting of Ex4 and mouse IgG heavy chain constant regions (Ex4/Fc) can exert biological effects of GLP-1, such as improving glycemic control and ameliorating manifestations in diabetic mice. The aim of this study was to determine whether Ex4/Fc is effective in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…GLP-1 also exerts a variety of biological actions independent of islet β cells, including reduction in gastric emptying, suppression of glucagon secretion and body weight sparing effects. Although controversial, previous studies showed that GLP-1 can also improve peripheral insulin sensitivity ( Liu et al, 2014 , 2016 ). Here, we demonstrate that GLP-1 improves insulin sensitivity of ER-stressed adipocyte through modulation of UPR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLP-1 also exerts a variety of biological actions independent of islet β cells, including reduction in gastric emptying, suppression of glucagon secretion and body weight sparing effects. Although controversial, previous studies showed that GLP-1 can also improve peripheral insulin sensitivity ( Liu et al, 2014 , 2016 ). Here, we demonstrate that GLP-1 improves insulin sensitivity of ER-stressed adipocyte through modulation of UPR.…”
Section: Discussionmentioning
confidence: 99%
“…Following drug treatment as indicated, cells were lysed in RIPA buffer (1% Nonidet P-40, 0.5% sodium deoxycholate, and 0.1% SDS in PBS) supplemented with protease and phosphatase inhibitor mixtures. Forty to fifty micrograms of cell lysate protein was resolved by SDS-PAGE and immunoblotted as described previously ( Liu et al, 2014 ). The proteins were transferred to PVDF membrane and immunoblotted with primary antibodies overnight.…”
Section: Methodsmentioning
confidence: 99%